Pavement and Noise Reduction Performance of Open-Graded Asphalt Friction Course Improved by Waste Tire Crumb Rubber. (9th September 2021) - Wang, Ya; Wang, Xianguang; Zhang, Liwen
Abstract : To further reveal the road performance and noise reduction performance of open-graded friction course (OGFC), the crumb rubber prepared by adding waste tires were considered, and the performance requirements of the material were put forward. To avoid the influence of rubber particle swelling on aggregate, the special gradation and mix proportion of OGFC mixture were designed, and the particle size of 4.75 mm was proposed as the control size. The test results show that the aggregate forms a good embedded structure. The resilient modulus, deformation performance, and fatigue performance of R-OGFC asphalt mixture with different crumb rubber contents were studied. According to the test results, the rubber particle content under the best road performance and noise reduction effect was proposed. The results show that, after adding a certain amount of crumb rubber, the performance of asphalt mixture has been greatly improved, especially the dynamic stability has been improved by 84%. Although the resilient modulus has decreased by 10%, the creep performance has decreased by 37%, and the fatigue life has decreased by 31% (2% rubber content), the noise reduction can reach 3.6–8.6 dB, and the noise reduction performance is significant. This shows that the best content of rubber particles is between 1.5% and 2%, and the R-OGFC mixture modified by rubber has a good application prospect.